AN ANALYSIS OF TRANSLATION TECHNIQUES USED BY SUBTITLE WRITER OF THE ANGRY BIRDS MOVIE - Zulhan Hadi; Untung Waluyo; Baharuddin (Journal of English Education Forum (JEEF), 2021)
This study was aimed to find out the translation techniques used by the translator in English-to-Indonesian subtitle of The Angry Birds movie. It was also aimed to find out the most dominant type of translation technique used in the subtitle. To understand the phenomenon of the study, this research applied qualitative method by using purposive sampling technique. A set of 233 utterances of the main characters was used as data of the study and analyzed based on the 18 translation techniques proposed by Molina and Albir (2002). The results show that there are 9 of 18 translation techniques used by the translator that included: established equivalent, linguistic compression, discursive creation, modulation, literal translation, compensation, calque, transposition, and borrowing. The established equivalent is the most dominant translation technique used in the subtitle that comprises 44.6% of the total utterances (104 of 233 utterances).